CircASH1L inhibits ferroptosis and enhances cisplatin resistance by sponging miR-515-5p to regulate cell cycle-related CDCA7/RRM2 in ovarian cancer cells - Feng, Lu; Zou, Xinru; Tang, Longyu; Yuan, Yijun; He, Tianwen; Su, Bin; Tang, Ying; Wang, Jiang; Liu, Kang; Li, Jun (Frontiers in Pharmacology, 2025)
BackgroundPlatinum chemotherapy, particularly cisplatin, has been the standard treatment for ovarian cancer. However, the development of resistance to cisplatin is a significant challenge during treatment. Circular RNAs (circRNAs) are a class of non-coding RNAs with a circular structure and have been implicated in regulating ferroptosis and chemoresistance. Despite the increasing recognition of circRNAs in cancer progression, the role of circASH1L in ferroptosis and cisplatin resistance in ovarian cancer remains poorly understood.MethodsRNA sequencing (RNA-seq) was utilized to identify differentially expressed circRNAs in ovarian cancer cells. Cell survival and invasion were assessed using CCK-8 and transwell assays, while apoptosis, cell cycle progression, and lipid peroxidation were analyzed by flow cytometry. Levels of GSH, MDA, and iron ions were measured using appropriate kits. qRT-PCR and Western blot analyses were performed to evaluate the expression of relevant RNAs and proteins. The clinical relevance of circASH1L/miR-515-5p/CDCA7 axis in ovarian cancer patients was analyzed using public datasets. Molecular interactions were confirmed through dual-luciferase reporter assays, RNA immunoprecipitation (RIP), and co-immunoprecipitation (Co-IP). In vivo, the effects of circASH1L on ferroptosis and chemoresistance were evaluated using a xenograft mouse model.ResultscircASH1L expression was downregulated upon erastin treatment and significantly upregulated in cisplatin-resistant A2780/DDP and SKOV3/DDP cells. Silencing circASH1L reversed cisplatin resistance by reducing cell viability and invasion, while promoting apoptosis and ferroptosis. Mechanistically, circASH1L was found to act as a sponge for miR-515-5p, which in turn regulates the CDCA7/RRM2 axis. Rescue experiments demonstrated that inhibiting miR-515-5p or overexpressing CDCA7 blocked the effects of circASH1L silencing. Moreover, CDCA7 could interact with RRM2 and inhibit RRM2 degradation, which contributed to reducing cell cycle arrest and ferroptosis resistance. The clinical analysis showed circASH1L, and CDCA7/RRM2 expression was positive correlated with drug resistance and worse survival rate, while miR-515-5p expression was on the contrary. In vivo, silencing circASH1L enhanced cisplatin sensitivity by inducing ferroptosis.ConclusionOur study demonstrates that silencing circASH1L alleviates cisplatin resistance in ovarian cancer cells. The underlying mechanism involves the upregulation of miR-515-5p, which targets the CDCA7/RRM2 axis, leading to cell cycle modulation and the induction of ferroptosis. Targeting the circASH1L/miR-515-5p/CDCA7 pathway offers new insights into the relationship between ferroptosis and chemoresistance, presenting a promising strategy to overcome chemoresistance in ovarian cancer.